Moving towards a Treatable Traits model of care for the management of obstructive airways diseases. (October 2021) - Agusti, Alvar; Barnes, Neil; Cruz, Alvaro A.; Gibson, Peter G.; Heaney, Liam G.; Inoue, Hiromasa; Leather, David; Martinez, Fernando J.; McDonald, Vanessa M.; Oppenheimer, John; Papi, Alberto; Pavord, Ian D.; et al.
Abstract: Asthma and chronic obstructive pulmonary disease (COPD) are two prevalent chronic airways diseases. Both are complex and heterogeneous. Traditionally, clinical guidelines have advocated a stepwise approach to pharmacotherapy of asthma and COPD, but there is increasing realization that both require a more personalized and precise management approach. To this end, a management strategy based on the so-called Treatable Traits has been proposed. Emerging evidence suggests that this model improves relevant outcomes in patients with chronic airway diseases but further research is needed to guide implementation. This review discusses the challenges, opportunities, and hurdles that its implementation will have to face. Graphical abstract: Image 1 Highlights: The complexity and variability of airways diseases supports personalized treatment. A Treatable Traits (TT) model targeting measurable/treatable traits has been proposed. The TT model factors in variability and causes of airways diseases between patients. TT also addresses symptoms in pulmonary, non-pulmonary, behavioural/lifestyle areas. Evidence suggests a TT model of care will work; more study will guide implementation.